PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PEMASARAN MELALUI KEUNGGULAN BERSAING SEBAGAI VARIABEL MEDIASI PADA UMKM KEDAI KOPI DI CIKARANG UTARA KABUPATEN BEKASI - Umu Azizatul Latifah; RR. Wening Ken Widodasih; Kurbandi Satpatmantya BR (Jurnal Ilmiah Global Education, 2023)
The study aims to determine the effect of entrepreneurial orientation on marketing performance through competitive advantage as a mediating variable in UMKM Coffee Shops in North Cikarang, Bekasi Regency. The sampling method used was nonprobability sampling with a purposive sampling method with a sample of 100 respondents. Data collection used a questionnaire with a Likert measurement scale. The method used in this research is Structural Equation Modeling (SEM) analysis with Smartpls 3.3.3 software. The tests used are outer model analysis, inner model analysis and hypothesis testing. The results of the study explain that entrepreneurial orientation has a positive and significant effect on marketing performance with a p-value of 0.004, a t-statistic value of 2,857, competitive advantage has a positive and significant effect on marketing performance with a p-value of 0,000, a t-statistic value of 21,679, entrepreneurial orientation has an effect positive and significant impact on competitive advantage with a p-value of 0.000 with a t-statistic value of 14.185, and competitive advantage as a mediating variable strengthens the relationship between entrepreneurial orientation and marketing performance with a p-value of 0.000 with a t-statistic value of 12.620..